2022
DOI: 10.1038/s44161-022-00095-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of immunoglobulin E attenuates pulmonary hypertension

Abstract: Pulmonary hypertension (PH) is a severe cardiopulmonary disease characterized by pathological vascular remodeling in the lung. Immunoglobulin E (IgE) is known to participate in aortic vascular remodeling, but whether IgE mediates pulmonary vascular remodeling in PH is unknown. Here, we found serum IgE elevation in PAH patients, hypoxia-induced PH mice and monocrotaline (MCT)-induced PH rats.Combining animal model of PH with single-cell RNA sequencing, we found IgE production in the lung tissues of PH mice. Neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Here, higher expression was associated with better survival [ 12 ]. Although not measured in this cohort, previous studies reported elevated IgE levels in iPAH patients, due to skewed isotype switching induced by Th2 cytokines [ 25 , 26 ]. Few data are available regarding patients with CTD-PAH, with conflicting reports of elevated IgA [ 64 ] and decreased IgG [ 45 ] levels in SSc-PAH (compared to SSc without pulmonary hypertension).…”
Section: Effector Mechanisms Of B-cells In Pahmentioning
confidence: 84%
See 4 more Smart Citations
“…Here, higher expression was associated with better survival [ 12 ]. Although not measured in this cohort, previous studies reported elevated IgE levels in iPAH patients, due to skewed isotype switching induced by Th2 cytokines [ 25 , 26 ]. Few data are available regarding patients with CTD-PAH, with conflicting reports of elevated IgA [ 64 ] and decreased IgG [ 45 ] levels in SSc-PAH (compared to SSc without pulmonary hypertension).…”
Section: Effector Mechanisms Of B-cells In Pahmentioning
confidence: 84%
“…Preferential class-switching towards IgE, a hallmark of Th2 stimulation, is frequently noted in PAH. Increased IgE serum levels and IgE + B-cells are observed in the blood of PAH patients and the lungs of several experimental models [ 25 , 26 ].…”
Section: Activating Mechanisms Of B-cells In Pahmentioning
confidence: 99%
See 3 more Smart Citations